Pengalaman Indra dan Persepsi Manusia: Sebuah Kajian mengenai Sense of Place - Sidhi Pramudito; Ikaputra Ikaputra (RUAS)
Through interaction, humans build relationships and become part of the environment. The process of interaction will shape the experience of individual senses, memory, and perception on which to create a sense of place. This study aims to determine the process of creating the meaning of places based on perceptions received by the human senses. The method used is qualitative descriptive, with a case (Malioboro) within the scope of sensory experience and perception. Case study analysis uses adaptations of content analysis methods. The results showed that the sense of sight has an important role in responding to a stimulus, producing memory, and perception in a setting. The involvement of other senses besides the sense of sight in the creation of environmental settings is important because through the entire senses will be produced an increasingly specific, distinctive, and personal meaning of place. The resulting meaning will then become a long-term memory that can be expressed to the audience to further reinforce the collective meaning of the place.